2021
DOI: 10.3390/pr9071177
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Adsorbents for Cobalt Removal from Wastewater: A Bibliometric Analysis of Research Articles Indexed in the Scopus Database

Abstract: In this study, a combined technique of bibliometric and social network analysis was applied on research articles, related to the application of nano-adsorbents for cobalt removal from wastewater, published in Scopus database up to 2020. The results revealed that the first relative research article appeared in the Scopus database in the year 2002. The total output of research articles reached 214 in the year 2020. Published research articles of the years 2014–2020, added up to 83.6% of total articles. King Saud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Apart from their application in adsorption, materials based on transition metal-carbonaceous phase-clay minerals were successfully used as catalysts in the advanced oxidative degradation of various organic pollutants [34]. Although different transition metals were applied in adsorbent synthesis, cobalt is widely used because, as a bio-essential element, it does not cause major environmental concerns [35].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their application in adsorption, materials based on transition metal-carbonaceous phase-clay minerals were successfully used as catalysts in the advanced oxidative degradation of various organic pollutants [34]. Although different transition metals were applied in adsorbent synthesis, cobalt is widely used because, as a bio-essential element, it does not cause major environmental concerns [35].…”
Section: Introductionmentioning
confidence: 99%
“…For example, cobalt at high concentration can pose health risks, with symptoms related to asthma, and damage of liver, thyroid and heart. Cobalt has been reported to cause also genetic mutations in living organisms, while in other studies cobalt has been reported as a possible carcinogen 1 …”
Section: Introductionmentioning
confidence: 98%
“…Cobalt has been reported to cause also genetic mutations in living organisms, while in other studies cobalt has been reported as a possible carcinogen. 1 Wastewater treatment is one of the most important means of protecting the water environment from pollution. Due to its features of energy saving and ease of operation, the membrane process has become a significant and efficient technology for water purification, including municipal and industrial wastewater as well as seawater purification and desalination.…”
Section: Introductionmentioning
confidence: 99%